PERAN DISIPLIN DAN MOTIVASI KERJA TERHADAP PENINGKATAN KINERJA PEGAWAI PUPR SUKABUMI - Prakoso, Sugih; Mulyani, Rema; Eja, Eja (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
The research method used is an associative study with a quantitative approach. The main objective of this research is to determine the effect of work discipline and work motivation on employee performance at the Department of Public Works and Spatial Planning in Sukabumi City. With a total population of 200 people, the sample of this study consisted of 67 respondents determined using the Slovin formula. The research data were collected using a Likert scale questionnaire to measure the variables of work discipline, work motivation, and employee performance. The results of the study indicate that work discipline has a positive and significant partial effect on employee performance, with a t-value of 2,480 > t- table 1,997 and a significance level of 0,000 < 0,05. Work motivation also has a positive and significant effect on employee performance, as shown by a t-value of 5,999 > t-table 1,997 and a significance level of 0,000 < 0,05. Simultaneously, both variables have a significant effect on employee performance, with an F-value of 54,676 > F-table 3,14 and a significance level of 0,000 < 0,05. The Adjusted R2 value of 0,619 indicates that 61,9% of the variance in employee performance is influenced by these two variables. These findings highlight the importance of work discipline and work motivation as key factors in improving employee performance.